Pengaruh Citra Destinasi dan E-WOM di Media Sosial Instagram serta Persepsi Konsumen Terhadap Keputusan Berkunjung ke Objek Wisata B29 di Kabupaten Lumajang - Ainun Nur Illah; Raden Andi Sularso; Bambang Irawan (UPT Penerbitan Universitas Jember, 2019)
The research aims to analyze the effect of destination image and electronic word of mouth and consumer perceptions of visiting decisions probability to visit of object B29 in Lumajang The research approach used in this study is a quantitative research. The pulation in the research are all society from inside of Lumajang Regency and from outside of Lumajang Regency who have never visited B29 tourism object as many as 130 respondents. In this study the total number of indicator variables totaled 13. Data analysis method used in this research is logistic regression analysis. Hypotesis test use was showed that the destination image and electronic word of mouth and consumer perception have a significant influence on the decision to visit B29 tourism object in Lumajang Regency. Keywords: Destination Image, Electronic Word of Mouth, Consumer Perception, Visiting Decision.